2009
DOI: 10.1177/1934578x0900400501
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals and Health Benefits of Xanthohumol, a Natural Product Derived from Hops and Beer

Abstract: In recent years, there has been a growing interest in phenolic compounds and their presumed role in the prevention of various degenerative diseases, such as cancer and cardiovascular diseases. Xanthohumol, a prenylated chalcone from hops and beer, is among the phenolic compounds which have received the most attention in recent years. This compound has a range of interesting biological properties that may have therapeutic utility. Based on the health-promoting properties of xanthohumol, the production of a beer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 125 publications
0
89
0
3
Order By: Relevance
“…In vitro studies have indicated that these compounds are broad-spectrum cancer chemopreventive agents [6]. Based on the health-promoting properties of xanthohumol, production of beer enriched with this compound is of interest to brewing companies in order to provide consumers with a better product [7]. Major polyphenolic compounds in beer are listed in Box 14.1.…”
Section: Antioxidants Present In Beermentioning
confidence: 99%
“…In vitro studies have indicated that these compounds are broad-spectrum cancer chemopreventive agents [6]. Based on the health-promoting properties of xanthohumol, production of beer enriched with this compound is of interest to brewing companies in order to provide consumers with a better product [7]. Major polyphenolic compounds in beer are listed in Box 14.1.…”
Section: Antioxidants Present In Beermentioning
confidence: 99%
“…Recent research has examined the biological activities of single hop components, particularly XN. Anti-inflammatory, antioxidant, antilipoperoxidative activities as well as antiangiogenic, antiproliferative and apoptotic effects, mainly assessed in vitro studies, reasonably suggest a potential chemopreventive activity (Gerhauser et al, 2002;Magalhães, Carvalho, et al, 2009). In addition, XN displays broadspectrum anti-infective activity against several micro-organisms (Magalhães, Carvalho, et al, 2009;Nowakowska, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Anti-inflammatory, antioxidant, antilipoperoxidative activities as well as antiangiogenic, antiproliferative and apoptotic effects, mainly assessed in vitro studies, reasonably suggest a potential chemopreventive activity (Gerhauser et al, 2002;Magalhães, Carvalho, et al, 2009). In addition, XN displays broadspectrum anti-infective activity against several micro-organisms (Magalhães, Carvalho, et al, 2009;Nowakowska, 2007). The reported beneficial health effects of XN have attracted attention in the brewing community concerning the production of XN enriched hop extracts and beers (Biendl, Methner, Stettner, & Walker, 2004;Magalhães, Dostalek, Cruz, Guido, & Barros, 2008;Wunderlich, Zürcher, & Back, 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The female inflorescences of hops ("hop cones") are used as a raw material in beer production, contributing to beer bitterness and aroma. During wort boiling, XN is largely converted into its isomeric flavanone, isoxanthohumol (IXN), a reason why very low content of XN can be found in beer [2,3]. In the past few years, the brewing industry has been interested in producing XN-enriched beers, mainly due to the recognized health benefits.…”
Section: Introductionmentioning
confidence: 99%